Capital estrangeiro e desenvolvimento econômico: cinco décadas do investimento direto estrangeiro no Brasil - Costa, Maria Roselene B. (2008)
The intention of the work is to characterize the evolution and the impact of the Direct Foreign Investment (IDE) in the Brazilian economic development. The period delimited for the analysis is the years between the decades of 1950 and 1990. Considering the boom in the flow of IDE directed to the Brazilian economy in recent years, it was searched to collate the different presented periods, in order to investigate the contribution of these resources in the different cycles of economic development of Brazil